OPINI MAHASISWA TERHADAP WEBSITE UNIVERSITAS MUHAMMADIYAH SIDOARJO SEBAGAI MEDIA INFORMASI - Zaqqiyatul Ifadah; Ainur Rochmaniah (Universitas Muhammadiyah Sidoarjo, 2014)
The aim of this research is to describe the students’ opinion of the website quality as an information media at University of Muhammadiyah Sidoarjo. The population of this research consists of 4.260 students of University of Muhammdiyah Sidoarjo. Random proposional technique is used as a technique sampling of this research which takes 97 repondences as the samples. The technique of data analysis used in this research is descriptive statistic. To interpret the data the perception value is also used as the guideline. The results of this research indicate that the use quality and information quality of website as an information media at University of Muhammadiyah Sidoarjo are less good. The interaction quality of website as an information media at University of Muhammadiyah Sidoarjo is not good and overall the respondence impression of website at University of Muhamamdiyah Sidoarjo is also not so good.